O discurso sobre a aula de matemática: articulando vozes na revista Nova Escola - Ferreira, Carlos Eduardo da Silva [UNESP] (2015)
This work promotes debates on the discourses vehiculated by the educational magazine Nova Escola, through the perspective of the Dialogic Discourse Analysis. The editions used are those from March/1986 to December/2012. We investigated how the comprehensions about the movement of circulation and voices emergence are built. These understandings reframe the concepts about the Math class in the Nova Escola magazines. How do discourses attributed to math teachers unfold in relation to the class event? How are they materialized through the history of this periodical in the Nova Escola sections? How can we establish discursive relations between these voices and the discourses vehiculated by the official curricular proposals documents engendered in the political-educational field? By analyzing discourses that refer to math teaching (lesson plans, articles/reporters) developed by Nova Escola - with teachers' interaction in this mediatic space, e.g. readers response - we can build a data network of how the direct and radial (diffuse) relations between the triad teacher-student-knowledge during the class moment process are thought, reflected and prepared . Focusing that, we may relate discussions not strictly to the notion of Math classes in the used editions of the publication, but also direct reflections about the class moment itself, how it is faced/interpreted and conducted. In addition to select which discourses can give us bases to perform a discursive analysis, we pose some other questions in the development of our work, as how does the Math teacher's discourse is expressed in certain genres internal to the magazine? Hence, we intend to over-raise possible changes of focus/perspectives yaw that we believe Nova Escola employed. In order to accomplish it, we worked to analyze the Math teacher's voices instauration rearrangements on teaching techniques/practices shown in the magazine, as well as the structural-discursive...